Diffuse Correlation Spectroscopy (DCS) and Diffuse Optical Spectroscopy (DOS) for photodynamic therapy monitoring. - Siti Raudhah Matyasir. (2013)
Photodynamic Therapy (PDT), is a cancer therapy that is still on clinical trial, is used in this project. PDT is an emerging modality that has many advantages such as non-invasive, low side effects, low scarring, low risk of resistance, cost effective and shorter treatment time.